Management of Thoracic Wall Trauma in a Goat: A Case Report - , Rohit Kumar; Sanjay; Lokesh, Amit Kumar, Deepti Sharma, Deepti Bodh, Adarsh Kumar (Archives of Current Research International, 2025)
Thoracic wall rupture is a rare but serious condition in ruminants which can occur becauseof trauma, leading to respiratory distress, subcutaneous emphysema and compromised thoracic integrity.The present communication describes the successful surgical management of thoracic rupture in a goat. The case was presented with a history of a wound on the right lateral thoracic region with the respiratory distress after returning of the animal from grazing. On clinical examination and radiography, it was diagnosed as a case of thoracic rupture with the presence of haemothrax. So, an immediate surgical repair of the thoracic rupture was done and a chest tube for intermittent thoracocentesis was placed to drain the blood from the pleural space postoperatively. The chest tube was taken out after 3 days and the sutures were removed after 14 days. The animal recovered uneventfully.